2021
DOI: 10.1093/plcell/koab055
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary gain of oligosaccharide hydrolysis and sugar transport enhanced carbohydrate partitioning in sweet watermelon fruits

Abstract: How raffinose (Raf) family oligosaccharides (RFOs), the major translocated sugars in the vascular bundle in cucurbits, are hydrolyzed and subsequently partitioned has not been fully elucidated. By performing reciprocal grafting of watermelon (Citrullus lanatus) fruits to branch stems, we observed that Raf was hydrolyzed in the fruit of cultivar watermelons but was backlogged in the fruit of wild ancestor species. Through a genome-wide association study (GWAS), the alkaline alpha-galactosidase ClAGA2 was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 73 publications
1
57
1
Order By: Relevance
“…Several SWEETs and UmamiTs from various species are known to be expressed in different sink tissues ( Figure 4 ; e.g. Kryvoruchko et al, 2016 ; Zhen et al, 2018 ; Jeena et al, 2019 ; Wang et al, 2019 ; Ren et al, 2021 ). Impaired activity of SWEETs or UmamiTs causes defects in basic physiological processes reflecting their broad role.…”
Section: Roles For Sweets and Umamits In Phloem Unloadingmentioning
confidence: 99%
“…Several SWEETs and UmamiTs from various species are known to be expressed in different sink tissues ( Figure 4 ; e.g. Kryvoruchko et al, 2016 ; Zhen et al, 2018 ; Jeena et al, 2019 ; Wang et al, 2019 ; Ren et al, 2021 ). Impaired activity of SWEETs or UmamiTs causes defects in basic physiological processes reflecting their broad role.…”
Section: Roles For Sweets and Umamits In Phloem Unloadingmentioning
confidence: 99%
“…In addition, raffinose family oligosaccharides are also major sugars translocated in the vascular bundle in cucurbits. ClAGA2, ClSWEET3 (a plasma membrane-localized clade I hexose transporter) and ClTST2 function in raffinose hydrolysis, transmembrane sugar transport and sugar storage in vacuoles, respectively, thereby contributing to the derivation of sweet watermelon from non-sweet ancestors during domestication (Ren et al 2021). Moreover, it was reported recently that MdERDL6-1, a tonoplast glucose/H ?…”
Section: Sugar Transportmentioning
confidence: 99%
“…Genome editing of five genes in the carotenoid metabolic pathway was conducted to promote lycopene biosynthesis, and at the same time inhibit its conversion to βand αcarotene (Li et al 2018f). Using CRISPR/cas9 technology, Ren et al (2020Ren et al ( , 2021 revealed several important node genes of sugar accumulation in the process of watermelon domestication, which laid a foundation for watermelon improvement in the future.…”
Section: The Development Of Crispr/cas9 Genome Editing Technologymentioning
confidence: 99%